Beyond the bamboo ceiling: How ethnic collaborative networks facilitate Chinese inventors’ knowledge remittances - Hua Zhang; Jia Liu; Chunhui Cao (PLoS ONE, 2026)
Previous research on the “bamboo ceiling” has focused on how ethnic homophily limits career advancement for East Asian immigrants. However, less is known about how their ethnic collaborative networks as U.S. Chinese immigrant inventors may facilitate knowledge remittances to their home countries. Drawing on social network theory, this study investigates two core network positions—centrality and structural holes (i.e., connecting otherwise unconnected co-inventors)—and their effects on knowledge remittances. Ethnic knowledge utilization serves as the mediator, while inventors’ past performance acts as the moderator. We test the proposed relationships using a unique dataset of patents in the integrated circuit industry. Results show that ethnic knowledge utilization mediates the relationship between network positions (centrality and structural holes) and knowledge remittance. Moreover, past performance significantly moderates the mediating paths: high-performing inventors more effectively exploit structural holes to facilitate knowledge remittance. They also strengthen the curvilinear effect of centrality, accelerating knowledge remittance at optimal centrality levels but triggering an earlier decline beyond these thresholds due to stronger path dependency. These findings not only support policies for leveraging diaspora knowledge networks but also advance the literature by establishing a more nuanced, attribute-based micro-foundation for understanding high-skilled migration’s impact on home-country development.